Efficacy and safety of the collagenase of the bacterium clostridium histolyticum for the treatment of capsular contracture after silicone implants: ex-vivo study on human tissue - Fischer, Sebastian; Hirche, Christoph; Diehm, Yannick; Nuutila, Kristo; Kiefer, Jurij; Gazyakan, Emre; Bueno, Ericka M.; Kremer, Thomas; Kneser, Ulrich; Pomahac, Bohdan (PLOS ONE, 2016)
Background The fibrotic capsule that surrounds silicone implants consists mainly of collagen. The FDA-approved collagenase of the bacterium clostridium histolyticum provides a reasonable treatment option. Safety and efficacy at the female breast site must be evaluated before clinical utilization. Materials and Methods We incubated 20 samples of fibrotic capsule as well as 12 full thickness skin grafts harvested from the female breast site for 24 hours with different doses of collagenase. Outcome measures involved histological assessment of thickness and density of the capsule tissue as well as the skin grafts. Furthermore, we performed a collagen assay and immunohistochemistry staining for collagen subtypes. Results Collagenase treatment was able to degrade human capsule contracture tissue ex-vivo. The remaining collagen subtype after degradation was type 4 only. 0.3 mg/ml of collagenase was most effective in reducing capsule thickness when compared with higher concentrations. Of note, effectiveness was inversely related to capsule density, such that there was less reduction in thickness with higher capsule densities and vice versa. Furthermore, the application of 0.3mg/ml collagenase did not lead to thinning or perforation of full thickness skin grafts. Conclusion Adjustment of collagenase dose will depend on thickness and density of the contracted capsule. A concentration of 0.3mg/ml seems to be safe and effective in an ex-vivo setting. The remaining collagen subtype 4 is suitable to serve as a neo-capsule/acellular tissue matrix. Collagenase treatment for capsular contracture may soon become a clinical reality.
Gesehen am 02.06.2020